Squamous cell carcinoma of the lung showing a ground glass nodule on high-resolution computed tomography associated with pneumoconiosis: a case report - Yuriko Terada; Masaaki Sato; Hiroyuki Abe; Hideki Kuwano; Kazuhiro Nagayama; Jun-ichi Nitadori; Masaki Anraku; Jun Nakajima (Surgical Case Reports)
Abstract Background Adenocarcinoma with lepidic growth pattern presents as a ground glass nodule (GGN) on high resolution computed tomography (CT), whereas peripheral pulmonary squamous cell carcinoma (SCC) usually presents as a solid nodule. We herein report a rare case of pulmonary SCC extending along the alveolar lumen representing as a GGN on a CT scan in a patient with pneumoconiosis. Case presentation A 77-year-old man with pneumoconiosis was found to have a gradually enlarging GGN in the right lower lobe of the lung on CT. An adenocarcinoma of the lung was suspected. The GGN was successfully resected by thoracoscopic segmentectomy. Pathological examination of the resected specimen was pathologically diagnosed as a stage IA SCC extending along the alveolar lumen. The patient had no evidence of recurrence 19 months after surgery. Conclusions SCC should be included in the differential diagnosis of peripherally located GGNs, especially in patients at high risk of SCC of the lung such as those with pneumoconiosis.